Targeting Diverse Wounds and Scars: Recent Innovative Bio‐design of Microneedle Patch for Comprehensive Management - Zhuang, Ze‐Ming; Wang, Yong; Feng, Zi‐Xuan; Lin, Xiao‐Ying; Wang, Zheng‐Cai; Zhong, Xin‐Cao; Guo, Kai; Zhong, Yu‐Fan; Fang, Qing‐Qing; Wu, Xiao‐Jin; Chen, Jian; Tan, Wei‐Qiang (Small (Weinheim an der Bergstrasse, Germany), 2024)
Wounds and the subsequent formation of scars constitute a unified and complex phased process. Effective treatment is crucial; however, the diverse therapeutic approaches for different wounds and scars, as well as varying treatment needs at different stages, present significant challenges in selecting appropriate interventions. Microneedle patch (MNP), as a novel minimally invasive transdermal drug delivery system, has the potential for integrated and programmed treatment of various diseases and has shown promising applications in different types of wounds and scars. In this comprehensive review, the latest applications and biotechnological innovations of MNPs in these fields are thoroughly explored, summarizing their powerful abilities to accelerate healing, inhibit scar formation, and manage related symptoms. Moreover, potential applications in various scenarios are discussed. Additionally, the side effects, manufacturing processes, and material selection to explore the clinical translational potential are investigated. This groundwork can provide a theoretical basis and serve as a catalyst for future innovations in the pursuit of favorable therapeutic options for skin tissue regeneration. This work surveys various microneedle patches applied in recent years targeting diverse wounds and scars, exploring the potential to improve specific types of wound healing and mitigate pathological scarring. The therapeutic efficacy, management of related symptoms, side effects, materials, and manufacturing methods are assessed, providing insights into future research and clinical translation.